Error Analysis of English Sentence Structure in Students’ Written Paragraphs - Sundari, Dike; Hidayah, Jumatul; Edy, Sarwo; Esmianti, Farida (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This research aimed to find out the types of sentence structure errors in English paragraphs written by tertiary English students and the factors causing the errors. This research employed an explanatory mixed-method design. Fourth-semester students from the English department of IAIN Curup were engaged as the subjects of this research. Positivism-governed document analyses and constructivism-based interviews were conducted to solicit the data as desired. The quantitative findings garnered from document analyses endorsing a ready-to-use construct proposed by Dulay, Burt, and Krashen (1982), revealed that there were four types of sentence structure errors students made, namely omission, addition, misformation, and misordering. Those types of errors were exhibited in a proximate composition which meant that the students had compatible difficulties in terms of the four types of errors. As uncovered from students' writing works, the four types of errors were found in the domains of words, phrases, and clauses. Subsequently, the qualitative findings, elicited from interviews, demonstrated that the factors of sentence structure errors extended to students' mother tongue interference, overgeneralization in the use of English rules and norms, and the lecturer's teaching material delivery and method. Anchored in the data gained, this research discussed the data from the perspective of interlanguage theory, wherein some reviews of SLA and EFL pedagogy-related theories were offered to help lower the factors causing English sentence structure errors in writing skills.Â Keywords:Â Errors, Sentence Structure, English writing skill